Inactivation of the Lateral Entorhinal Area Increases the Influence of Visual Cues on Hippocampal Place Cell Activity - Scaplen, Kristin M.; Ramesh, Rohan N.; Nadvar, Negin; Ahmed, Omar J.; Burwell, Rebecca D. (Frontiers in Systems Neuroscience, 2017)
The hippocampus is important for both navigation and associative learning. We previously showed that the hippocampus processes two-dimensional (2D) landmarks and objects differently. Our findings suggested that landmarks are more likely to be used for orientation and navigation, whereas objects are more likely to be used for associative learning. The process by which cues are recognized as relevant for navigation or associative learning, however, is an open question. Presumably both spatial and nonspatial information are necessary for classifying cues as landmarks or objects. The lateral entorhinal area (LEA) is a good candidate for participating in this process as it is implicated in the processing of three-dimensional objects and object location. Because the LEA is one synapse upstream of the hippocampus and processes both spatial and nonspatial information, it is reasonable to hypothesize that the LEA modulates how the hippocampus uses 2D landmarks and objects. To test this hypothesis, we temporarily inactivated the LEA ipsilateral to the dorsal hippocampal recording site using fluorophore-conjugated Muscimol (FCM) 30 minutes prior to three foraging sessions in which either the 2D landmark or the 2D object was back-projected to the floor of an open field. Prior to the second session we rotated the 2D cue by 90 degrees. Cues were returned to the original configuration for the third session. Compared to the Saline treatment, FCM inactivation increased the percentage of rotation responses to manipulations of the landmark cue but had no effect on information content of place fields. In contrast, FCM inactivation increased information content of place fields in the presence of the object cue, but had no effect on rotation responses to the object cue. Thus, LEA inactivation increased the influence of visual cues on hippocampal activity, but the impact was qualitatively different for cues that are useful for navigation vs. cues that may not be useful for navigation. FCM inactivation also led to reductions in both frequency and power of hippocampal theta rhythms, indicative of the loss of functionally important LEA inputs to hippocampus. These data provide evidence that the LEA is involved in modulating how the dorsal hippocampus utilizes visual environmental cues.